The real property in the system of the objects of Civil Law (Journal of actual problems of jurisprudence, 2018)
This article devotes to a place of real property objects in the system of objects of civil law. The object of civil rights is where civil legal relationship occurs. In the Republic of Kazakhstan there is an active formation and development of the market of real property. The property takes an important place in civil circulation. The specificity of the legal regime of real estate is the limitation of rights in relations developing between the entities over real estate. Key words: objects of civil rights, real estate, legal property regime, the real estate market.